Mainstreaming human nutrition in livestock interventions: lessons learnt from a capacity building workshop for the Sahel region - Domínguez Salas, Paula; Kauffman, D.; Breyne, C.; Alarcón, Pablo (2016)
Location: Sahel What we know: Animal-source foods (ASFs) are a rich source of bioavailable nutrients. Even where livestock is central to livelihoods, livestock production is rarely considered as a key nutritional resource of poor populations. What this article adds: An FAO-led regional workshop was held in Senegal to capitalise on existing experiences and knowledge on linkages between livestock and human nutrition in the Sahel and strengthen the capacity of governments and humanitarian stakeholders for nutrition-sensitive programming in this sector. A total of 57 nutrition and/or livestock experts working in Burkina Faso, Chad, Mali, Mauritania, Niger and Senegal or at regional level participated. The workshop involved formal training, team work (to identify livestock impact pathways to malnutrition) and experience-sharing (detailed country case studies). Discussions found that, while high importance was awarded to integration, it was not a priority for either sector. Participants identified a number of ways to optimise the nutrition impact of interventions, including targeting, understanding the cultural specificities of ASF and their nutritional properties, and considering nutrition at the context-analyses and study-design stages. Risk factors for negative impact included food safety issues and high cost of interventions. Recommendations for follow-up included creation of a Community of Practice specific to livestock and nutrition.